2014
DOI: 10.1002/bies.201400066
|View full text |Cite
|
Sign up to set email alerts
|

Mild cold‐stress depresses immune responses: Implications for cancer models involving laboratory mice

Abstract: Physiologically accurate mouse models of cancer are critical in the pre-clinical development of novel cancer therapies. However, current standardized animal-housing temperatures elicit chronic cold-associated stress in mice, which is further increased in the presence of tumor. This cold-stress significantly impacts experimental outcomes. Data from our lab and others suggests standard housing fundamentally alters murine physiology, and this can produce altered immune baselines in tumor and other disease models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 84 publications
1
32
0
1
Order By: Relevance
“…Additionally, we opted to group house our mice during CJL conditioning rather than individually house mice. We did this because of emerging literature that housing mice individually may impose an additional stress on the animals that could confound our interpretation of SeV infection after CJL 43, 49 . Nevertheless, it is possible that our CJL protocol is milder than previous procedures, and may therefore understate the effects of jet lag on viral bronchiolitis.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we opted to group house our mice during CJL conditioning rather than individually house mice. We did this because of emerging literature that housing mice individually may impose an additional stress on the animals that could confound our interpretation of SeV infection after CJL 43, 49 . Nevertheless, it is possible that our CJL protocol is milder than previous procedures, and may therefore understate the effects of jet lag on viral bronchiolitis.…”
Section: Methodsmentioning
confidence: 99%
“…The epidemic scale was correlated with the minimum temperature (CC = -0.526) and temperature difference (CC = 0.606) in January. Low temperature causes cold stress, which depresses immune responses (13,14). Furthermore, cold stress due to temperatures <09 C causes death from respiratory disease in humans (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…She showed that mice housed at ST were less able to control Panc02 tumors compared to mice housed under TT conditions, as well as mice housed in ST that were given cisplatin. Increases in MDSCs and Tregs were found in ST mice compared to animals housed in TT (55, 56). A possible mechanism for the susceptibility of ST-housed mice is the production of norepinephrine as administration of propranolol, a β-blocker, led to the reversal of the ST-susceptibility to tumor challenge (52).…”
Section: Metabolism In Immunotherapymentioning
confidence: 94%